2019
DOI: 10.1002/pro.3779
|View full text |Cite
|
Sign up to set email alerts
|

ConSurf‐DB: An accessible repository for the evolutionary conservation patterns of the majority of PDB proteins

Abstract: Patterns observed by examining the evolutionary relationships among proteins of common origin can reveal the structural and functional importance of specific residue positions. In particular, amino acids that are highly conserved (i.e., their positions evolve at a slower rate than other positions) are particularly likely to be of biological importance, for example, for ligand binding. ConSurf is a bioinformatics tool for accurately estimating the evolutionary rate of each position in a protein family. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 45 publications
1
121
0
Order By: Relevance
“…To understand the interplay between evolutionary, topological, and dynamic signatures of the SARS-CoV-2 spike glycoprotein trimer, the sequence conservation profiles are computed to identify regions of high conservation and variability ( Figure 3 ). The sequence conservation ConSurf approach 52 56 was used to determine the residue-based conservation score profiles in which the low score is associated with the most conserved position in the protein. Consistent with previous studies, 108 110 this analysis showed that residues in the S1 domain are considerably less conserved than the S2 fusion domain.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the interplay between evolutionary, topological, and dynamic signatures of the SARS-CoV-2 spike glycoprotein trimer, the sequence conservation profiles are computed to identify regions of high conservation and variability ( Figure 3 ). The sequence conservation ConSurf approach 52 56 was used to determine the residue-based conservation score profiles in which the low score is associated with the most conserved position in the protein. Consistent with previous studies, 108 110 this analysis showed that residues in the S1 domain are considerably less conserved than the S2 fusion domain.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify these observations, we performed sequence alignment analysis and highlighted differences between SARS-CoV and SARS-CoV-2 sequences ( Figure 2 ). ConSurf approach has shown a robust performance in evolutionary analysis of proteins and the latest version of this method [ 38 , 39 ] was used in our study. The evolutionary analysis yielded an overall sequence identity of 78%.…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies confirmed these assertions revealing small but important changes in the RBM residues of SARS-CoV-RBD and SARS-CoV-2-RBD proteins [ 21 , 22 , 23 , 24 , 25 , 26 ]. We utilized two different sequence conservation measures Consurf score [ 38 , 39 ] and KL sequence conservation score [ 43 , 44 , 45 , 46 , 47 ] to identify regions of high conservation and characterize in some details the extent of conservation and variability of the binding interface residues ( Figure 4 ). We analyzed the results of sequence analysis in the context of structural and functional information, particularly to quantify the conservation patterns of the hotspot residues and uncover evolutionary origins of SARS-CoV-2 binding selectivity with ACE2.…”
Section: Resultsmentioning
confidence: 99%
“…For both the TRI5 p and TRI8 p structures, ConSurf-DB (ConSurf Data Base [ 88 , 89 ]; ) enabled structure modelling based on conserved sites unlike PDB structure models. Regions of high to low conservation were mapped onto the structures and a 3D rendering was generated for chain A and B depending on the enzyme.…”
Section: Methodsmentioning
confidence: 99%